Experimental research of the dynamic behavior of the natural gas suspension pipeline aerial crossing during pigging process. (November 2020) - Wu, Xia; Niu, Shuhao; Li, Changjun; He, Yufa
Abstract: Suspension pipeline aerial crossings (SPAC) are mainly used to carry pipeline segments over large obstacles that are not suitable for trenchless technologies. It may suffer great vibrations and displacements during the pigging process due to the dynamic pigging loads and insufficient constraints from cables. Based on similarity criteria, an experimental scale model based on the Nujiang natural gas SPAC was designed and established. The vibration and displacement of the scale model were measured under different pigging velocities and liquid deposit volumes. The experimental results reveal that the natural gas SPAC vibrates during the pigging process, but the displacement versus time forms a U curve instead of a sinusoidal like curve. The extremum of the displacement is positively related to the pigging velocity and liquid deposit volume. In particular, the extremum increases by 0.37% with a 1% increase in the pigging velocity, while the displacement increases by 0.62% with a 1% increase in the liquid deposit volume. Under certain pigging conditions, or with damaged constraint components, the displacement extremum could be unacceptable. A low pigging velocity and a short time interval between two pigging operations are suggested to guarantee the safety of the natural gas SPACs. Besides, based on the experimental data, an empirical formula is developed to obtain the SPAC displacement-time curve with consideration of the span length, the pipeline diameter, the pigging velocity, the length and holdup of the liquid column. This formula can help to determine a suspicious displacement overrun, and to develop a data basis for choosing a safe pigging scheme of SPACs. This research provides insightful information to understand the mechanism of the SPAC's dynamic response as well as a practical tool to calculate the SPAC's displacement during the pigging process. Highlights: A scale model of natural gas suspension pipeline aerial crossings (SPAC) was established to study its pigging induced dynamic behavior. SPACs vibrate due to the pig shocking loads on the elbows but the displacement is mainly caused by the gravity loads of the pig and liquid. The vibration and displacement are positively related to the pigging velocity and liquid volume. An empirical formula is developed to obtain the SPAC displacement-time curve.